Immunologic Assessment of Patients Treated with Bovine Fibrin as a Hemostatic Agent - Carroll, John F; Moskowitz, Keith A; Edwards, Niloo M; Hickey, Thomas J; Rose, Eric A; Budzynski, Andrei Z (Thrombosis and Haemostasis, 1996)
Twenty-one cardiothoracic surgical patients have been treated with fibrin as a topical hemostatic/sealing agent, prepared from bovine fibrinogen clotted with bovine thrombin. Serum samples have been collected before treatment with fibrin and postoperatively between 1 and 9 days, 3 and 12 weeks, and 6 and 8 months. The titers of anti-bovine fibrinogen antibodies, measured by ELISA specific for immunoglobulins IgG or IgM, increased to maximal values after about 8 or 6 weeks, respectively. After 8 months, IgG titers were on average 20-fold lower than the mean maximal value, while IgM titers returned to the normal range. IgG was the predominant anti-bovine fibrinogen immunoglobulin as documented by ELISA, affinity chromatography and electrophoresis. Anti-bovine fibrinogen antibodies present in patients reacted readily with bovine fibrinogen, but did not cross-react with human fibrinogen as measured by ELISA or by immunoelectrophoresis. A significant amount of antibodies against bovine thrombin and factor V has been found, many cross-reacting with the human counterparts. No hemorrhagic or thrombotic complications, or clinically significant allergic reactions, occurred in any patient, in spite of antibody presence against some bovine and human coagulation factors. The treatment of patients with bovine fibrin, without induction of immunologic response against human fibrinogen, appeared to be an effective topical hemostatic/sealing measure.